Flow Sorting-Assisted Optical Mapping - Šimková, Hana; Tulpová, Zuzana; Cápal, Petr (Methods in molecular biology (Clifton, N.J.), 2023)
Optical mapping-a technique that visualizes short sequence motives along DNA molecules of hundred kilobases to megabase in size-has found an important place in genome research. It is widely used to facilitate genome sequence assemblies and analyses of genome structural variations. Application of the technique is conditional on availability of highly pure ultra-long high-molecular-weight DNA (uHMW DNA), which is challenging to achieve in plants due to the presence of the cell wall, chloroplasts, and secondary metabolites, just as a high content of polysaccharides and DNA nucleases in some species. These obstacles can be overcome by employment of flow cytometry, enabling a fast and highly efficient purification of cell nuclei or metaphase chromosomes, which are afterward embedded in agarose plugs and used to isolate the uHMW DNA in situ. Here, we provide a detailed protocol for the flow sorting-assisted uHMW DNA preparation that has been successfully used to construct whole-genome as well as chromosomal optical maps for 20 plant species from several plant families.
Keywords: Nuclei; průtoková cytometrie; rostliny; Restriction Mapping; Flow Cytometry; Chromosomes, Plant; Flow cytometry and sorting; HMW DNA preparation; Optical mapping; Plants; Sequence Analysis, DNA; Chromosomes; sekvenční analýza DNA; restrikční mapování; genom rostlinný; Genome, Plant; Bionano genome map; chromozomy rostlin; ultralong high-molecular-weight DNA